1999
DOI: 10.2165/00007256-199927010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Tools Used in the Study of Eccentric Contraction???Induced Injury

Abstract: The objective of this review is to evaluate the measurement tools currently used in the study of eccentric contraction-induced muscle injury, with emphasis on their usefulness for quantifying the magnitude and duration of the injury and as indicators of muscle functional deficits. In studies in humans, it was concluded that measurements of maximal voluntary contraction torque and range of motion provide the best methods for quantifying muscle injury. Similarly, in animal studies, the in vitro measurement of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
545
4
43

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 669 publications
(634 citation statements)
references
References 0 publications
42
545
4
43
Order By: Relevance
“…A common method to quantify functional recovery of skeletal muscle following injury is to measure its ability to generate peak isometric torque at various time points during the repair processes (Warren et al 1999). For example, we have shown that reductions in isometric torque can exceed 50 % in the days post-injury and take approximately 2 weeks to fully recover (Baumann et al 2014a(Baumann et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…A common method to quantify functional recovery of skeletal muscle following injury is to measure its ability to generate peak isometric torque at various time points during the repair processes (Warren et al 1999). For example, we have shown that reductions in isometric torque can exceed 50 % in the days post-injury and take approximately 2 weeks to fully recover (Baumann et al 2014a(Baumann et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos prévios questionam a relação entre a DMIT 11 e o extravasamento de CK com outros marcadores de dano muscular, indicando que estes marcadores não são bons preditores da magnitude de dano muscular induzido pelo exercício 5,11,12,14 . Um dos questionamentos em relação a utilização da CK como marcador indireto de dano muscular é pelo fato da molécula de CK possuir grande massa molecular (80 kDa) e, portanto, teria dificuldade em entrar no endotélio microvascular 15 .…”
Section: Discussionunclassified
“…Desta forma, um pequeno grau de dano muscular que não altere significativamente a permeabilidade da membrana, não faria com que houvesse extravasamento de CK para a corrente sanguínea. O presente estudo, mesmo classificando os indivíduos em grupos baixos e altos respondedo- Indivíduos Média cluster ± DP res à queda de CVM, não observou diferenças significantes na atividade sérica de CK corroborando com estudos que indicam que a análise do extravasamento de proteínas intramusculares na corrente sanguínea deve ser desencorajado para propostas de quantificação de prejuízos funcionais e/ou do grau de dano muscular induzido por EE 12,14 . No que concerne a DMIT, Nosaka et al 11 demonstraram com uma amostra de 110 homens jovens que a dor muscular tardia possui correlações fracas ou mesmo inexistentes com outros marcadores indiretos de dano muscular (e.g.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Eccentric movement exacerbates the response to unaccustomed exercise due to the forcible lengthening of myofibrils and associated disruption of sarcomeres, which is unique to eccentric contraction 1, 2, 3. Histological examination of muscle samples following concentric and eccentric contractions has previously revealed structural damage in only the eccentrically exercised muscles 4.…”
mentioning
confidence: 99%